Duration of Sleep, Perception of Hunger and Satiety and Weight Gain during Pregnancy - Yolanda Botello Moreno (Jounal of Negative and No Positive Results, 2018)
Objective: To determine whether the duration and interruption of sleep, perception of hunger-satiety influence the excessive weight gain in Mexican pregnant women. Materials and Methods: Cross-sectional design, with 305 pregnant women, recruited in a primary care clinic. The duration of sleep was evaluated by interview and a hunger and satiety perception scale was used. Weight was obtained before and during pregnancy. The linear regression model was used to analyze the data. Results: The average number of hours that pregnant women slept was 9.04 hours per night, 83% interrupted sleep and 16.7% gained excessive gestational weight. The pre-gestational body mass index and sleep interruption explained the gestational weight gain. Conclusion: Intervening in factors that influence the interruption of sleep in pregnant women can contribute to prevent excessive weight gain and prevent maternal and child complications.